Extension of the Universal Force Field for Metal–Organic Frameworks - Coupry, Damien E; Addicoat, Matthew A; Heine, Thomas (Journal of chemical theory and computation, 2016)
We have extended the Universal Force Field for Metal–Organic Frameworks (UFF4MOF) to cover all moieties present in the most extensive framework library to date, i.e., the Computation-Ready Experimental (CoRE) database (Chem. Mater. 2014, 26, 6185). Thus, we have extended the parameters to include the fourth and fifth row transition metals, lanthanides, and an additional atom type for sulfur, while the parameters of original UFF and of UFF4MOF are not modified. Employing the new parameters significantly enlarges the number of structures that may be subjected to a UFF calculation, i.e., more than doubling accessible MOFs of the CoRE structures and thus reaching over 99% of CoRE structure coverage. In turn, 95% of optimized cell parameters are within 10% of their experimental values. We contend these parameters will be most useful for the generation and rapid prototyping of hypothetical MOF structures from SBU databases.